PELURUHAN NUKLEON KIDAL MENJADI PION DAN POSITRON KIDAL DALAM MODEL KORESPONDENSI SKALAR-SPINOR - , FIKA FAUZI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
We propose an extension of standard model through the addition of a Scalar- Spinor Correspondence (SSC) concept, where for each spinor in the standard model (plus right-handed neutrino) there is a corresponding particle in the scalar sector with the same gauge group representation assignment and hypercharge quantum number. This model introduce six new-scalars, in which two are Higgs scalars ( dan ) and four are leptoquark scalars (1, 2, !, and ). The leptoquark mediate four nucleon decays which does not occur in the standard model (low-energy scale). Two of them are left-handed proton decaying into neutral pion and left-handed positron